The influences of absorptive capacity and social capital on knowledge transfer - Samy, Naresh Kumar; Che Rose, Raduan; Abdul Muien, Nurul Fatiha (The Clute Institute, 2009)
This study investigated the current business practices in Japanese electrical and electronics manufacturing subsidiaries as well as the influences of both absorptive capacity and social capital on knowledge transfer within the firms’ intra-MNC network in the wake of full AFTA implementation in 2018. Results showed that employees are generally satisfied with the current practices in these subsidiaries with relation to the eight dimensions being studied; learning system, training, communication, reward, promotion, compensation, trust and centrality. This study also found that absorptive capacity has definite but small relationship with knowledge transfer, while social capital bears much more substantial relationship with the former.